AB0510 Alphacalcidol Therapy Decreases GSH, SOD and Catalase Levels in Erythrocytes of Rheumatoid Arthritis Patients. (9th June 2015) - Zivanovic Radnic, T.; Simic-Pasalic, K.; Sefik-Bukilica, M.; Misirlic Dencic, S.; Stojkovic, T.; Damjanov, N.; Vojinovic, J.
Abstract : Background: Low vitamin D serum levels have been associated with several autoimmune diseases including rheumatoid arthritis (RA). Vitamin D deficiency enhances oxidative stress that plays a substantial role in pathogenesis of autoimmune diseases. Objectives: Because erythrocytes are extremly vulnerabile to oxidative stress, the aim of this research was to analyse the effect of twelve weeks long alphacalcidol therapy in patients with RA on erythrocytes' glutathione (GSH), superoxide dismutase (SOD) and catalase levels, as an oxidative stress markers. Methods: In ten patients with active RA (DAS28(SE) score >3.2) of both sexes, age 53.78±12.01 alphacalcidol (2μg/day) was added to previously applied therapy (stable dose of methotrexate, without any steroid therapy) during three months. Blood samples were taken before and after 12 weeks of alphacalcidol therapy. GSH, SOD and catalase levels in isolated and lysed erythrocytes were determined mannualy, using spectrophotometry method. Hemoglobin (Hb) levels were measured in lysed erythrocytes using biochemical analyser (Beckman coulter AcT diff) and levels expressed as μmol/g Hb for GSH and U/g Hb for catalase and SOD. In addition, parameters of inflammation (serum C-reactive protein (CRP) and sedimentation rate (SE)) were determined and disease activity was assessed using DAS28 (SE) score. Laboratory safety assessment of the study drug was evaluated monthly. Student's t-test was used for statistical analysis. Results: Average erythrocytes GSH level before treatment was 6.0±2.3 μmol/g Hb and it decreased to 3.7±1.3 μmol/g Hb (p=0.02) after treatment. Futhermore, initial catalase levels of 1412.3±840.2 U/ g Hb dropped to 211.3±119.1 U/g Hb (p=0.01) after twelve weeks of alphacalcidol therapy. Although slight reduction in SOD levels was observed after therapy, it was statistically insignificant. Significant clinical impovement was observed, DAS28(SE) was before treatment 5.81±0.89 and decreased to 4.31±1.03 (p=0.001), and CRP level of 28.41±28.16 dropped to 10.03±11.68 (p=0.000). Conclusions: Decreased levels of erythrocytes' GSH and catalase in RA patients after 12 weeks of alphacalcidol therapy indicate that alphacalcidol induced antioxidative effect. We assume that alphacalcidol lead to reduction of H2 O2 production in erythrocytes and therefore decreased the need for antioxidative enzymes catalase and glutathione peroxidase activity. Antioxidative effect of alphacalcidol was in line with good clinical outcome in patients. Disclosure of Interest: None declared